Impact of IoT and Embedded System on Semiconductor Industry A Case Study - Tareq, Abdulla Al; Rana, Md Juel; Mostofa, Md Riad; Rahman, Md Sadiqur (Control Systems and Optimization Letters, 2024)
The fast growth of Internet of Things (IoT) devices and advances in embedded systems are causing major changes in the semiconductor business. Examining major trends, obstacles, and opportunities, this case study investigates how embedded systems, and the Internet of Things are affecting the semiconductor business. It explores how semiconductor technology has developed to satisfy the needs of Internet of Things applications, focusing on connectivity options, low-power design, and sensor integration. The report examines how technological advancements, competitive tactics, and market dynamics are reshaping the semiconductor industry. Because IoT devices are frequently integrated into wearable technology or deployed in remote areas, power efficiency becomes essential. Using sophisticated low-power design approaches and power management features, semiconductors must be engineered to function with the least amount of power possible. Miniaturization of semiconductor technology is required due to the requirement for increasingly compact and smaller devices in embedded systems and the Internet of Things. The strategic implications for semiconductor businesses navigating this dynamic ecosystem are highlighted by drawing insights from industry data, market analysis, and case studies. Through an analysis of actual cases and market developments, this case study offers insightful insights into the changing role of semiconductor technology in facilitating the Internet of Things revolution.